Analisis Penerapan Sak Etap Pada Laporan Keuangan Koperasi Satuan Brimob Polda XYZ - Fransiscus Amonio Halawa (Sekolah Tinggi Manajemen Pariwisata dan Logistik Lentera Mondial, 2024)
The purpose of this study was to determine and analyze the application of Financial Accounting Standards for Entities Without Accountability (SAK ETAP) in the financial statements of the East Kalimantan Police Mobile Brigade Unit Cooperative in 2019. This research was conducted at the East Kalimantan Police Mobile Brigade Unit Cooperative, with the problem being investigated, the authors focused on the application of SAK-ETAP covering the recognition of: Assets, Debts, Revenues, Expenses, Profit/Loss; measurement: Historical Expenses and Fair Value; presentation of: Balance Sheet, Profit/Loss, Changes in Equity and Profit/Loss and Retained Earnings, Cash Flows and Notes to Financial Statements; Disclosure for the period 2019. The analytical tool in this study compares the financial statements of the East Kalimantan Police Mobile Brigade Unit Cooperative with SAK ETAP. Based on the results of the research, the financial statements of the East Kalimantan Police Mobile Brigade Unit Cooperative in 2019 are sufficient in accordance with the Financial Accounting Standards for Entities Without Accountability (SAK ETAP). However, the financial reporting data made by the East Kalimantan Police Mobile Brigade Unit Cooperative in 2018 and 2019 based on SAK ETAP is still lacking, namely the financial statements only consist of 2 components, the balance sheet element only consists of 6 items and the profit/loss element consists of 2 items. Keywords: Financial Accounting Standards for Entities Without Accountability, Cooperative Financial Statements.